Addressing strategic human resource management practices for TQM: the case of an Indian tire manufacturing company. Issue 1 (3rd September 2021) - Verma, Pratima; Kumar, Vimal; Mittal, Ankesh; Gupta, Pardeep; Hsu, Sung Chi
Abstract : Purpose: This study aims to identify SHRM (strategic human resource management) essential practices for the TQM (total quality management) program regarding an Indian tire manufacturing company and formulate an inclusive interrelationship to prioritize them. Design/methodology/approach: Semistructured interview with ten experts from the company was made to give SHRM practices scores. The SLR (systematic literature review) and TOPSIS (technique for order of preference by similarity to ideal solution) techniques are used to establish the model for 12 key practices and rank them afterward. Findings: The findings clearly show that strategic planning and staffing, teamwork and leadership development have appeared as the top three essential practices. Simultaneously, performance measurement and evaluation, work design and analysis and promotion are identified as the bottom three practices. These essential practices are identified as contributing attributes. Practical implications: The findings prioritize the SHRM practices as contributing attributes that help other tire manufacturing industries identify their key practices. Moreover, it provides the necessary inputs comprised of ten experts' decisions to become more active and well prepared. Originality/value: The novelty of this study is to identify the key practices by using SLR and measured by the TOPSIS method to rank and consider a tire manufacturing company as a case-based approach to gain high productivity and competitive advantage.